Globalization, production and poverty - Rhys Jenkins (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2005)
The impact of globalization on poverty is a matter of keen debate but empirical work in this area has been dominated by cross-country regressions. This paper attempts to link the more macro impacts of globalization, particularly as manifested through the impact on employment, with the micro level analysis of poverty at the individual and household level. The link is provided through the analysis of specific value chains (horticulture, textiles and garments) which are driven by changes at the global level but which have impacts at the local level in terms of employment and poverty. The paper reports on studies carried out in four countries—Bangladesh, Kenya, South Africa and Vietnam—which have all become more integrated with the global economy in recent years. The approach presented gives no universal conclusions about the impact of globalization on poverty but shows that outcomes are highly context dependent. – globalization ; employment ; poverty ; value chains ; Bangladesh ; Kenya ; South Africa ; Vietnam ; textiles ; garments ; horticulture
Keywords: F02; F14; F16; O53; O55; 330; Armut; Globalisierung; Gartenbau; Textilhandwerk; Bangladesch; Kenia; Südafrika; Vietnam; Betriebliche Wertschöpfung